Students’ Satisfaction with the Choice of Public Transport Mobility in UiTM Puncak Alam - Dzulkalnine, Natasha; Anuar , Marhani Mohamed; Hafit , Nor Intan Adha (Information Management and Business Review, 2024)
Transportation is essential for facilitating movement and contributing to economic development. This study aims to measure student satisfaction with public transportation mobility at UiTM Puncak Alam. Understanding the level of satisfaction derived from transportation services is crucial for enhancing student experiences. The main focus of this research is to identify the factors influencing student satisfaction with public transport services, specifically examining reliability, convenience, frequency, and safety in UiTM Puncak Alam. A correlation study was conducted to explore the relationships between these factors and student satisfaction. The research utilized a non-probability convenience sampling method, distributing a questionnaire to 217 students from the Faculty of Business and Management. Data collection occurred over three months, from October 2022 to December 2022, using online questionnaires. The findings indicate that comfort, frequency, and safety significantly influenced student satisfaction. Numerous students expressed their dissatisfaction with the old buses, inconsistent service schedules, and safety issues. These elements were discovered to influence students’ selection of public transportation and their overall contentment. The research also highlighted concerns like bus conditions, driver behavior, and punctuality, all of which affect student satisfaction and academic achievement. Based on these findings, the study suggests increasing the bus fleet, enhancing service frequency, and strengthening safety measures to better address student needs and boost their overall satisfaction with public transportation at UiTM Puncak Alam.